Conectados e a leitura em ambientes digitais de estudantes nos anos iniciais do ensino fundamental I - Maikel Fontes de Melo (2019)
This work aimed at identifying reading skills of students of the early years of elementary school in digital environments. In order to do that, a study was carried out to compare the performance of pairs of students who participated of an intervention made by a project for digital literacy with other students who did not participate on those activities. To perform such research, data were collected with a program that records the screen, sound and image of the search process. The students, divided in pairs, had to perform a search for educational toys. The analysis was made from the videos recorded by the program Camtasia and their transcripts. The data was analyzed according to a matrix of skills based on Dias & Novais (2009). As expected, the results showed that the group that had the project intervention achieved a better performance compared to the group that did not participate in the project. Some skills were identified in both groups pointing that students also develop a practical digital literacy outside the school environment. However, we can consider that the training period provides a better use of digital technologies and conscious use of the available tools with a more reliable access and a transformer view.